1996
DOI: 10.5636/jgg.48.541
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Kinetic Properties of Plasmoids and Their Boundary Regions

Abstract: Based on GEOTAIL/LEP observations in the distant magnetotail, this paper reports on several new features of velocity distribution functions of electrons and ions within a plasmoid and at its boundary. Here we use the term'plasmoid' in a wider meaning than usual in spite of the presence of significant magnetic By fields. In the lobe, as expected from MHD simulations of magnetic reconnection processes, cold plasmas are pushed away from the plasma sheet before the arrival of plasmoids, while after the plasmoid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Zong et al (1997) reported quasi-periodic energetic ion bursts in the deep tail (X GSM =−96 R E ) associated with plasmoid-like structures with bipolar signature in the B z -component and in the B y -component. Mukai et al (1996) reported details of the counter-streaming ions and electron distributions found within a plasmoid and at its boundary. Frank et al (1995) directly determined the field-aligned current densities using the plasma measurement in the core of a magnetotail flux rope with a cross-sectional size of 0.7 R E , at X GSM ∼96 R E .…”
Section: Flux Ropes and Plasmoidsmentioning
confidence: 99%
“…Zong et al (1997) reported quasi-periodic energetic ion bursts in the deep tail (X GSM =−96 R E ) associated with plasmoid-like structures with bipolar signature in the B z -component and in the B y -component. Mukai et al (1996) reported details of the counter-streaming ions and electron distributions found within a plasmoid and at its boundary. Frank et al (1995) directly determined the field-aligned current densities using the plasma measurement in the core of a magnetotail flux rope with a cross-sectional size of 0.7 R E , at X GSM ∼96 R E .…”
Section: Flux Ropes and Plasmoidsmentioning
confidence: 99%
“…These beams are often observed when a satellite crosses the plasma sheet boundary (PSBL) (Parks et al, 1998;Lui et al, 1994;Frank et al, 1994;Eastman et al, 1984). Another class of observed non-Maxwellian distribution functions is for counterstreaming ions (CSIs) along the magnetic field line, often observed inside the plasmamoids/flux ropes (Mukai et al, 1996;Hoshino et al, 1997). However, detailed observations of particle distribution functions in the vicinity of the reconnection layer are still rare.…”
Section: Introductionmentioning
confidence: 99%
“…The slow shocks were observed in the distant tail (X<−100 R E ) on the lobe-plasma sheet boundary (e.g. Saito et al, 1995) and on the plasmoid boundaries at X∼−100 R E (Mukai et al, 1996). Recently, Eriksson et al (2004) reported observations of reconnection related shocks in the near-Earth tail.…”
mentioning
confidence: 96%
“…Zong et al, 2004), the term "plasmoid" is usually used for closed magnetic structures (magnetic islands), manifested as the northsouth bipolar variation of the magnetic field, embedded into tailward bulk flow (e.g. Mukai et al, 1996;Ieda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%